2015
DOI: 10.11607/ofph.1463
|View full text |Cite
|
Sign up to set email alerts
|

Amplified Brain Processing of Dentoalveolar Pressure Stimulus in Persistent Dentoalveolar Pain Disorder Patients

Abstract: Aims (1) To determine the brain regions activated by dentoalveolar pressure stimulation in persistent dentoalveolar pain disorder (PDAP) patients, and (2) to compare these activation patterns to those seen in pain-free control subjects. Methods A total of 13 PDAP patients and 13 matched controls completed the study. Clinical pain characteristics and psychosocial data were collected. Dentoalveolar mechanical pain thresholds were determined with a custom-made device over the painful area for patients and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…A coordinate-based meta-analysis investigating brain responses to orofacial pain stimuli in healthy controls revealed consistent activations in bilateral SII [12]. Previously, when applying noxious dentoalveolar stimuli to PDAP patients and controls with matched subjective stimulus intensity, we found greater activation in right SII in PDAP patients relative to controls [39].…”
Section: Sfmri Cortical Analysismentioning
confidence: 51%
See 1 more Smart Citation
“…A coordinate-based meta-analysis investigating brain responses to orofacial pain stimuli in healthy controls revealed consistent activations in bilateral SII [12]. Previously, when applying noxious dentoalveolar stimuli to PDAP patients and controls with matched subjective stimulus intensity, we found greater activation in right SII in PDAP patients relative to controls [39].…”
Section: Sfmri Cortical Analysismentioning
confidence: 51%
“…One study revealed decreased brain activations in regions of the frontoparietal attention network in TMD patients subjected to forearm heat [24] while another found no brain activation differences between TMD patients and controls in response to thumbnail pressure pain [33]. In a previous sfMRI study done by our group, noxious dentoalveolar pressure stimuli was applied to patients with persistent dentoalveolar pain disorder (PDAP), a chronic orofacial pain condition affecting the dentoalveolar structures [39] which is commonly comorbid with TMD pain [40]. Compared to controls, PDAP patients exhibited a greater extent of brain activations over several brain areas including SI, SII, insula, prefrontal cortex, and thalamus.…”
Section: Introductionmentioning
confidence: 99%
“…While the posterior insula is part of the lateral pain system, the anterior insula is part of the mesial pain system and is involved in affective pain processing 35 , 37 . Similarly, elevated insular activity was found during ‘amplified pain processing’ in persistent dentoalveolar pain disorder (PDAP) patients (compared to matched controls) induced by dentoalveolar pressure stimulation 38 . In this context, it is interesting that reductions of insular activity associated with decreased pain percepts under orthodontic treatment were reported: in patients with orofacial pain, mandibular splint therapy caused a decrease in left anterior insula activity and the magnitude of the decrease in perceived pain correlates with the magnitude of the decrease in insular activation 39 .…”
Section: Discussionmentioning
confidence: 97%
“…However, a different study that tested CPM in PDAP cases and controls did not find such endogenous pain inhibition impairment (Baad-Hansen, List, Kaube, et al, 2006). Other study supporting central amplification of pain in PDAP patients showed greater activation in brain regions related to the sensory-discriminative and cognitive components of pain perception in patients relative to pain-free controls following matched dentoalveolar pressure intensity stimulation during functional magnetic resonance imaging (Moana-Filho, Bereiter, & Nixdorf, 2015). Put together, these findings suggest dysfunction of endogenous pain modulation mechanisms and brain-related pain amplification following dentoalveolar mechanical painful stimulus (Moana-Filho et al, 2015;Nasri-Heir et al, 2015)…”
Section: Unmet Copc Characteristicsmentioning
confidence: 99%